2012
DOI: 10.1021/es3007854
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Kinetics of Polar Organic Compounds over Polyethersulfone Membranes in the Passive Samplers Pocis and Chemcatcher

Abstract: Passive samplers for polar organic compounds often use a polyethersulfone (PES) membrane to retain the particulate sorbent material (e.g., in a POCIS; polar organic chemical integrative sampler) or to reduce the sampling rate and thus extend the kinetic regime (e.g., in a Chemcatcher). The transport kinetics over the PES membrane are evaluated here in a short-term (6 days) and a long-term (32 days) experiment with POCIS and Chemcatchers. Passive samplers were placed in a channel with flowing river water that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 21 publications
12
128
2
Order By: Relevance
“…From these results, the authors concluded that analytes first adsorbed onto the membrane, then diffused through the membrane and finally accumulated on the disk. These results were in accordance with other observations showing that the use of a membrane induces a lag-time between sampler deployment and the beginning of accumulation [37,61]. Vermeirssen et al [61] observed a lag phase for compounds with log K ow higher than 2.0 (diuron and diazinon).…”
Section: Disks and Membranes: Assorted Mountings According To The Tarsupporting
confidence: 92%
See 3 more Smart Citations
“…From these results, the authors concluded that analytes first adsorbed onto the membrane, then diffused through the membrane and finally accumulated on the disk. These results were in accordance with other observations showing that the use of a membrane induces a lag-time between sampler deployment and the beginning of accumulation [37,61]. Vermeirssen et al [61] observed a lag phase for compounds with log K ow higher than 2.0 (diuron and diazinon).…”
Section: Disks and Membranes: Assorted Mountings According To The Tarsupporting
confidence: 92%
“…These results were in accordance with other observations showing that the use of a membrane induces a lag-time between sampler deployment and the beginning of accumulation [37,61]. Vermeirssen et al [61] observed a lag phase for compounds with log K ow higher than 2.0 (diuron and diazinon). Two experiments were conducted for 6 and 32 days and the estimated lag phases were slightly different, probably as a result of a temperature variation between the experiments (20.5°C and 13.8°C, respectively).…”
Section: Disks and Membranes: Assorted Mountings According To The Tarsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, membranes are needed to retain the sorbent in a POCIS. If Empore™ disks are used without a membrane, they will sample a wider range of chemicals and with higher sampling rates [12]. Low selectivity is very important when combining passive sampling with biological analysis, to prevent exclusion of unknown toxicants [13].…”
Section: Introductionmentioning
confidence: 99%